Review Of The Sharia Economic Approach To Tourism Promotions - Norvadewi Norvadewi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study uses qualitative methods and is descriptive in nature. As data sources, both primary and secondary data are used. using methods for data collection such as observation, interviews, and documenting. The Bandung Regency Tourism Office has created stages for its promotional plan as a result of this study, which includes marketing through sports, retail sales, public relations, and advertising. The Bandung Regency Tourism Office's promotion plan utilising electronic media, such as the internet, has been performing successfully. Additionally, the Bandung Regency Tourism Office has active accounts on Facebook and Instagram. The advertising plan for print media hasn't, however, been fully utilized. From a sharia economic perspective, the advertising strategy of the Bandung Regency Tourism Office can be defined based on Islamic economic principles in advertising and Islamic business ethics consisting of Honesty, Trust, Justice, and Istiqomah. The Tourism Office correctly supports Islamic principles in accordance with Islamic law.